Caracterização da gestão e de atividades de capacitação para o processo de desenvolvimento de produto alimentício: estudos de caso - Bosi, Mirela Guedes (Universidade Federal de São Carlos, 2003)
During the 90s, Brazilian market open to imported goods sets the beginning of food industry transformation in Brazil. Other factors led to competitiveness growth among food companies, such as: the development of new technology, and consumers knowledge and expectation level increase. Therefore, food companies were forced to seek for competitive advantage which allowed the differentiation of their products in the market. In this context, product development process (PDP) gains fundamental importance. Due to the importance of PDP in the food industry, this work seeks characterize the food product development process management. Besides, this work aims to characterize the capability to PDP. In order to reach these purposes, eight food companies and three organizations (ITAL, SENAI, and a consultant company) that backup food industry were studied. Three food companies were chosen out of the eight which were studied and were presented in this work. The chosen companies have a more structured PDP, which allows a discussion on capability building process. The findings showed that food companies follow a sequence of phases and activities during PDP. This sequence is very similar when food companies are compared with each other and with the theoretical background. Concerning capability, food companies see capability building restrict to courses, and to market fairs visiting. The organizations that backup food industry serve mainly small companies, which do not have either enough technical or managerial knowledge in order to develop a product. Therefore, we consider that food product development process management is based on technical aspects. However, a minimal of managerial structure has been started by the companies. Besides, the need to develop new products tends to make food companies put in resources to build capability.
Keywords: Desenvolvimento de novos produtos; Alimentos - indústria; Construção da capacitação; Processo de desenvolvimento de produto; Product development process; Food industry; Capability building; ENGENHARIAS::ENGENHARIA DE PRODUCAO